Validation of an instrument to measure the self-efficacy of university students in Metropolitan Lima - Ramos Ramírez, Julio César (2021)
The purpose of this research article is to evaluate the statistical attributes of an instrument designed to measure self-efficacy in university students from the public universities of Metropolitan Lima. The study was of a quantitative and cross-sectional approach. A probabilistic sample of 425 young university students from public universities of Metropolitan Lima was interviewed in November 2018. The self-efficacy measurement instrument consisted of ten items, each item consisted of the student's ability to face a thought or belief with four alternatives response. The items were discriminated with the Mann-Whitney test, the construct validation with confirmatory factor analysis, and the internal consistency reliability analysis with the Cronbach's alpha statistic. The results obtained showed that all the items presented significant discrimination, since in all cases the significance reached was below 1%, all the items were able to be grouped into a single factor, with which it was concluded that the instrument has construct validity. Finally, the reliability achieved was 0.852 higher than 0.7 and the elimination of any item did not significantly reduce the level of reliability, thus establishing that the instrument presents adequate reliability.